Quad based Sub-Cluster Head Selection for Energy Efficiency in Wireless Sensor Networks - Kumar, Bhawnesh; Kumar, Ashwani; Negi, Harendra Singh (International Conference on Parallel, Distributed and Grid Computing (PDGC ...), 2022)
Cluster heads are the primary consideration used in Wireless Sensor Networks (WSN) to transfer data from one point to another point. A wireless sensor network's energy usage can be decreased by minimizing the nodes to communicate with final point. Organizing the network into different clusters, each of which elects a node as the head of cluster, is one method for allowing information exchange between sensors. Nodes are frequently clustered into mainly non-overlapping clusters to assist scalability. In this paper, a quad based sub-clustering innovative architecture for an effective clustering in wireless sensor heads is proposed. In a quad based sub-clustering strategy using K-means clustering, each sensor node delivers data to its sub-cluster head before sending data to the base station, as opposed to directly sending data to cluster heads. This strategy is used to reduce node power usage. The framework for a wireless sensor network's energy conservation is the subject of this research article. The framework is designed so that the sub-cluster head will be chosen after the nodes have been grouped together. The energy consumption of quad based sub-clustering is relatively less than single clustering. Through this approach, can increase the energy level of sensor networks.